A case of steroid‐resistant cystitis as an immune‐related adverse event during treatment with nivolumab for lung cancer, which was successfully treated with infliximab. Issue 6 (24th September 2022) - Fukunaga, Hiroyuki; Sumii, Kenta; Kawamura, Shun; Okuno, Masato; Taguchi, Isao; Kawabata, Gaku
Abstract : Introduction: Immune checkpoint inhibitors are widely used in various cancers as a standard treatment. However, while various immune‐related adverse events related to immune checkpoint inhibitors have been reported, there are few reports of lower urinary tract symptoms. Case presentation: The patient was a 60‐year‐old man with primary lung cancer who was receiving long‐term nivolumab therapy. He was referred to our department due to the sudden onset of glans penile pain and micturition pain. We suspected non‐bacterial cystitis as an immune‐related adverse event caused by nivolumab and were able to treat it by administering prednisolone. While his symptoms and findings on cystoscopy recurred during prednisolone therapy, we were able to treat him again by administering an additional dose of infliximab. Conclusion: A few reports have described cases of immune checkpoint inhibitor‐induced cystitis for which prednisolone was effective. This report is the first to describe cystitis as a steroid‐resistant immune‐related adverse event.